THE CONCEPT OF THE REPORTING ENTITY AND DUAL MATERIALITY IN SUSTAINABLE REPORTING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
To determine the boundaries of the reporting entity in good faith, it is necessary to consider the rights of stakeholders. The sustainability report applies to the same reporting entity as the financial statements. Financial statements are prepared from the perspective of investors using financial materiality criteria. The inclusion of the direct and indirect business relationships of the entity allows for the expansion of the scope of materiality by assessing the significant impacts, risks and opportunities associated with its activities. They require assessment and justification of the decision to include them in the determination of materiality, which is differentiated into impact materiality and financial materiality. These circumstances are considered upstream and/or downstream in the value chain of the entity. There is a need to document the decision to include information about the value chain only in relation to the parts of this chain for which the issue is material. For sustainability reporting, the materiality principle is transformed into the principle of double materiality. Accordingly, the financial statements include a new component – ​​a sustainability report, part of the organization’s annual report. There is a transformation of the financial reporting related to sustainability into a separate, structured sustainability report, part of the organization’s annual activity report. Resources for preparing quality sustainability reports are found in using accounting methods for current reporting through a certain analytical approach and assessment of significant impacts, risks and opportunities. The methods of analysis and synthesis, observation and comparison, analogy, documentation and modeling are used. The implementation of the proposed analytical accounting facilitates the preparation of the sustainability report. The documents prepared to include information on the value chain provide evidentiary value of the decisions made for the organization’s sustainability.